Integrating technology with literacy: using teacher-guided collaborative online learning to encourage critical thinking - Alyson Simpson (Association for Learning Technology, 2010)
This paper reports on classroom-based research that was designed to monitor the integration of information and communication technology (ICT) in a teacherguided collaborative online learning context to encourage students' critical response to literary texts. The study investigates the premise that an ICT project where children read books and then use email communication to exchange responses with other learners will support critical thinking. Videos of classroom observations, journals and rap sheets were analysed for individual students' levels of critical awareness. Improvements in critical thinking were measured using linguistic analysis. Teachers and students were also interviewed for attitudes to technology use related to learning. Although there were gains in critical thinking, there was little student engagement with technology. The discussion problematises the integration of technology in the classroom through a repositioning of collaboration in a blended learning context known as book raps.